2002
DOI: 10.1038/sj.npp.1300071
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Corticotropin-Releasing Factor (CRF) and Vasopressin Concentrations Predict Pituitary Response in the CRF Stimulation Test: A Multiple Regression Analysis

Abstract: There is considerable evidence that stress-related psychiatric disorders, including depression and post-traumatic stress disorder (PTSD), are associated with hypersecretion of corticotropin-releasing factor (CRF) within the central nervous system (CNS). One line of evidence that is consistent with central CRF hypersecretion in these disorders is the blunted adrenocorticotropin hormone (ACTH) response to intravenous CRF administration, likely a consequence, at least in part, of downregulation of anterior pituit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 57 publications
1
14
0
3
Order By: Relevance
“…Indeed, lesions to the CeA produce an 80-85% decrease in CRFir in the region of the LC (Koegler-Muly et al, 1993). The elevation of CSF CRFir in HMS180 rats is consistent with reports from clinical studies of depression and abuse (Banki et al, 1987;De Bellis et al, 1993;Geracioti et al, 1992;Nemeroff et al, 1991;Newport et al, 2003). Taken together with our previous reports showing increased hypothalamic and median eminence CRFir in HMS180 animals , these findings suggest that CRF gene expression and peptide synthesis within the PVN and CeA-LC systems may represent a common target in animals exposed to what may be considered abnormal neonatal rearing conditions regardless of which end of the rearing spectrum they fall intoFmonotonous housing and care (ie HMS0) vs extended periods of neonatal maternal separation (ie HMS180).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Indeed, lesions to the CeA produce an 80-85% decrease in CRFir in the region of the LC (Koegler-Muly et al, 1993). The elevation of CSF CRFir in HMS180 rats is consistent with reports from clinical studies of depression and abuse (Banki et al, 1987;De Bellis et al, 1993;Geracioti et al, 1992;Nemeroff et al, 1991;Newport et al, 2003). Taken together with our previous reports showing increased hypothalamic and median eminence CRFir in HMS180 animals , these findings suggest that CRF gene expression and peptide synthesis within the PVN and CeA-LC systems may represent a common target in animals exposed to what may be considered abnormal neonatal rearing conditions regardless of which end of the rearing spectrum they fall intoFmonotonous housing and care (ie HMS0) vs extended periods of neonatal maternal separation (ie HMS180).…”
Section: Discussionsupporting
confidence: 87%
“…This pattern of hyperresponsiveness has also been reported in several nonhuman primate models of early adversity (Coplan et al, 1996;Smith et al, 2002) and in adult women with a history of prepubertal abuse (Heim et al, 2000(Heim et al, , 2002Heim and Nemeroff, 2001). Changes in nervous system CRF tone appear to be associated with these changes in HPA responsiveness, as illustrated by elevations in CSF CRFir in the adult HMS180 rats (Figure 2), in several primate models of early adversity (Coplan et al, 1996;Maestripieri et al, 2005), primates with fearful temperaments (Kalin et al, 2000), and in abused children as well as in adult women with a history of abuse (Heim and Nemeroff, 2001;Newport et al, 2003;Carpenter et al, 2004). Alternatively, we recently reported blunting of the diurnal cortisol rhythm in rhesus monkeys exposed to early adversity without accompanying changes in CSF CRFir (Sanchez et al, 2005).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Using the dexamethasone suppression test and the combined DEX/CRF test in MDD, a reduced feedback sensitivity of the HPA axis was shown and has been interpreted as reduction of GR functioning (Holsboer, 2000). In this context vasopressin has been also emphasized to play an important role in MDD (Scott and Dinan, 1998;Newport et al, 2003;Dinan et al, 2004). Other authors have demonstrated that GR signalling is reduced in depression, suggesting that the brain is in a state of glucocorticoid resistance (Pariante et al, 2004).…”
Section: Cortisol and Cognition In Mddmentioning
confidence: 99%
“…A resposta da ACTH ao teste do CRH está diminuída na depressão endógena e alguns trabalhos demonstram inclusive down regulation dos receptores CRHR-1, refletindo o aumento nos níveis de CRH (48).…”
Section: Depressão Maiorunclassified